National Policy for Fair and Sustainable Cities - Hales Dib, Patricio (Universidad de Chile. Facultad de Arquitectura y Urbanismo, 2013)
Presentation to the Presidential Advisory Committee for a National Urban Development Policy (Chile), containing Principles and Guidelines for Action for a "National Policy Fair and Sustainable Cities".